Bacterial Cholangitis, Cholecystitis, or both in Dogs. (20th May 2016) - Tamborini, A.; Jahns, H.; McAllister, H.; Kent, A.; Harris, B.; Procoli, F.; Allenspach, K.; Hall, E.J.; Day, M.J.; Watson, P.J.; O'Neill, E.J.
Abstract : Background: Bacterial cholangitis and cholecystitis are rarely reported, poorly characterized diseases in the dog. Objectives: To characterize the clinical features of these conditions. Animals: Twenty‐seven client‐owned dogs with bacterial cholangitis, cholecystitis, or both. Methods: Multicenter, retrospective cases series of dogs with bacterial cholangitis, cholecystitis, or both, presenting January 2000 to June 2011 to 4 Veterinary Schools in Ireland/United Kingdom. Interrogation of hospital databases identified all cases with the inclusion criteria; histopathologically confirmed cholangitis or cholecystitis and bile culture/cytology results supporting a bacterial etiology. Results: Twenty‐seven dogs met the inclusion criteria with approximately 460 hepatitis cases documented over the same study period. Typical clinical pathology findings were increases in liver enzyme activities (25/26), hyperbilirubinemia (20/26), and an inflammatory leukogram (21/24). Ultrasound findings, although nonspecific, aided decision‐making in 25/26 cases. The most frequent hepatobiliary bacterial isolates were Escherichia coli (n = 17; 16 cases), Enterococcus spp. (n = 8; 6 cases), and Clostridium spp. (n = 5; 5 cases). Antimicrobial resistance was an important feature of aerobic isolates; 10/16 E. coli isolates resistant to 3 or more antimicrobial classes. Biliary tract rupture complicated nearly one third of cases, associated with significant mortality (4/8). Discharged dogs had a guarded to fair prognosis; 17/18 alive at 2 months, although 5/10 re‐evaluated had persistent liver enzyme elevation 2–12 months later. Conclusion and Clinical Significance: Bacterial cholangitis and cholecystitis occur more frequently than suggested by current literature and should be considered in dogs presenting with jaundice and fever, abdominal pain, or an inflammatory leukogram or with ultrasonographic evidence of gallbladder abnormalities.